Reconstruction of treatment facilities for wastewater treatment at "Antonov" State Enterprise - Bychkov, Sergii A.; Kyriienko, Petro G.; Varlamov, Yevhenii M.; Betin, Oleksandr V.; Mirsultanova, Lyalya R. (Kyiv National University of Construction and Architecture, 2021)
The main priorities of Ukraine's foreign policy in the field of environmental protection have always been political and institutional rapprochement with the European Union (EU). In this regard, Ukraine has made commitments to gradually harmonize national legislation with EU legislation. Therefore, the "Directive 2000/60/EC of the European Parliament and of the Council establishing a framework for the Community action in the field of water policy" which aimed at improving the protection and improvement of the aquatic environment through specific measures to reduce discharges, emissions and losses of priority substances, as well as the cessation or elimination of discharges, emissions and losses of hazardous substances, currently requires active implementation. Therefore, the issue of reconstruction of wastewater treatment plants at the enterprise of SE "Antonov" is very relevant. An analysis of the operation of wastewater treatment plants at the enterprise of SE "Antonov" was performed. Today, the entire complex of treatment facilities needs reconstruction with design work to implement the latest technologies for extraction of petroleum products from water and surface wastewater treatment, as well as the organization of self-flowing water treatment regime. Measures for the reconstruction of treatment facilities are proposed. The technology of operation of treatment facilities on the principle of self-flowing water treatment regime is offered, which will allow saving energy resources. An improved technology for extraction of petroleum products, floating and suspended solids from wastewater, and purification of effluents for dissolved petroleum products removal is proposed. Proposed measures will improve the environmental situation in reservoirs where treated water flows.